Innovative brain tumor therapy nanoparticle-based therapeutic strategies - Caruso, Gerardo; Mero, Lucia; Caffo, Maria (Amersterdam : Elsevier Science, 2014)
Despite recent advances, therapeutic efforts have not been successful establishing a definitive strategy of treatment for brain gliomas, because of the presence of the blood-brain barrier. Innovative Brain Tumor Therapy presents a synopsis of the studies on nanoparticles as ideal devices for brain tumor treatment. Their nanometric size, electrostatic charge, and lipophilic characteristics allow them to penetrate into the brain tissue freely. Promising in-vitro results have been reported, but remain to be validated in humans. This title focuses on the blood-brain barrier pathophysiology in brain tumors, and the possibilities of overcoming this with nanoparticle-based systems. Relevant patents of nanoparticles used as drug delivery carriers are also reported, as well as future scenarios in nanoparticles and stem cells.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Brain -- Tumors; Nanoparticles -- therapeutic use; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Electronic books